Mediastinal malignant mesothelioma discovered in a patient with dysphagia - Dario Amore; Simona Massa; Umberto Caterino; Dino Casazza; Albina Palma; Carlo Curcio (Respirology Case Reports, 2020)
Key message A mediastinal mass in patients with a history of asbestos exposure should raise the suspicion of malignant mesothelioma.